Online Auto Selection of Tuning Methods and Auto Tuning PI Controller in FOPDT Real Time Process-pH Neutralization. (June 2017) - Akshay, Naregalkar; Subbulekshmi, D.
Abstract: This paper aims to design an algorithm to identify Transfer Function of First Order Plus Dead Time (FOPDT) process by using Process Reaction Curve(PRC) identification method, auto selection of tuning methods using Ziegler- Nichols(Z-N), Astrom-Hagglund (A-H), Tsang-Rad(T-R), Fruehauf(FF) and Internal Model Controller (IMC), ITAE-1 tuning rules ITAE -1 for set point tracking(ITAE-1 SP) and disturbance rejection (ITAE-1 DR) and updating PI Controller parameters calculated for selected tuning method to meet optimized controller parameters. The performance of different tuning methods for various case studies of FOPDT processes were simulated and analyzed first and then real time plant- pH neutralization was controlled with proposed algorithm implemented in LabVIEW software.